(untitled) (Third Sector Social Economic Review, 2019)
The main purpose of this study is to determine whether there is a relationship between employee perceptions of organizational justice and intentions to leave work. In this field study, 150 private sector employees selected by sample method easily from firms operating in Kastamonu province were included in the sample. Frequency, percentage, factor, reliability and validity analyzes were used in order to reveal organizational justice and intention to leave work. Within the research; Regression analysis was used to examine the effect of employees’ perceptions of organizational justice and intention to leave work, and Correlation analysis was conducted to investigate the relationship between process, distribution, and interaction dimensions of organizational justice. As a result of the findings obtained with the analysis, it was concluded that there is a positive and meaningful relationship between employees’ perceptions of organizational justice and intention to leave work. In this context, the dimensions of organizational justice perception are the result of the intentions of employees to leave work.